2016
DOI: 10.1007/s00204-016-1772-1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of organophosphorus compounds in view of an increasing terrorist threat

Abstract: The implementation of the Chemical Weapon Convention (CWC), prohibiting the development, production, storage and use of chemical weapons by 192 nations and the ban of highly toxic OP pesticides, especially class I pesticides according to the WHO classification, by many countries constitutes a great success of the international community. However, the increased interest of terrorist groups in toxic chemicals and chemical warfare agents presents new challenges to our societies. Almost seven decades of research o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 128 publications
0
54
0
Order By: Relevance
“…pralidoxime (2-PAM) or its analogues: HI-6, obidoxime, MMB4. However, efficacy of these oximes is limited by steric constraints of an impacted active center gorge limiting pyridinium aldoxime attack, poor oral bioavailability, rapid clearance, and their inability to rapidly cross the blood-brain-barrier (BBB)(68). Recent clinical trials using pesticide-poisoned individuals have shown uneven clinical benefits with these oximes (911).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…pralidoxime (2-PAM) or its analogues: HI-6, obidoxime, MMB4. However, efficacy of these oximes is limited by steric constraints of an impacted active center gorge limiting pyridinium aldoxime attack, poor oral bioavailability, rapid clearance, and their inability to rapidly cross the blood-brain-barrier (BBB)(68). Recent clinical trials using pesticide-poisoned individuals have shown uneven clinical benefits with these oximes (911).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, as OP threats have spread widely due to terrorism and to increased agricultural use of pesticides, research has focused on the development of two types of countermeasures: (i) prophylactic stoichiometric and catalytic bio-scavengers (2,1217), an advanced candidate being butyrylcholinesterase (BChE) that has been shown to prevent OP toxicity in several animal models, and (ii) novel centrally acting, bioavailable oxime reactivators that can restore inhibited AChE activity in the brain post-OP exposure (4,7,8). Because the pharmacokinetics following parenteral delivery of large doses of stoichiometric bioscavengers of high molecular weight, such as BChE, are suboptimal for immediate post-exposure and longer term protection (17), administration of aerosolized (aer) rHuBChE via the pulmonary route is also under consideration to provide a protective pulmonary shield against inhaled volatile agents (1819).…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that Afghan girl schools may have been the target of terrorist attacks with OPC pesticides, but these allegations are controversial (Bartholomew, Lockery, & Najm, 2016;Masson & Nachon, 2017). Moreover, media reports suggest that the terrorist group ISIS may have stolen and employed sarin in Libya (Worek, Wille, Koller, & Thiermann, 2016). OPCs therefore continue to represent a worrying threat to civilians and rescue teams.…”
mentioning
confidence: 99%
“…Cholinesterases are found in two isoforms, AChE (EC 3.1.1.7) and butyrylcholinesterase (BChE), EC 3.1.1.8. Compounds that can inhibit cholinesterases may impact the body positively or negatively and, therefore, be either explored as method of warfare or therapeutically [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Of 22mentioning
confidence: 99%